Leaf trait variation is similar among genotypes of Eucalyptus camaldulensis from differing climates and arises in plastic responses to the seasons rather than water availability - Asao, Shinichi (The New phytologist, 2020)
© 2020 The Authors New Phytologist © 2020 New Phytologist Trust.